Parallel implementation of the PML algorithm for truncating finite-difference time-domain grids - Ramadan, Omar; Akaydin, Oyku (IEEE, 2006)
Three dimensional parallel implementation of the Perfectly Matched Layer (PML)formulations are presented for truncating Finite-Difference Time-Domain (FDTD) Grids. The FDTD computational domain is divided into subdomains using two-dimensional topology and the interprocessor communication operations between the subdomains are carried out by using the Message Passing Interface (MPI) library. The validity of the proposed algorithm is shown through numerical simulations carried out for a point source radiating in three-dimensional domains of different sizes and performed on a network of PCs interconnected with Ethernet.
4th IEEE/ACS International Conference on Computer Systems and Applications (AICCSA-06) -- MAR 08-11, 2006 -- Sharjah, U ARAB EMIRATES
Keywords: Perfectly Matched Layer; Maxwells Equations